2006
DOI: 10.1093/jn/136.2.384
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Restriction Alters Lipoprotein Metabolism by Modifying VLDL, LDL, and HDL Subfraction Distribution and Size in Overweight Men

Abstract: To determine the effects of carbohydrate restriction (CR) with and without soluble fiber on lipoprotein metabolism, 29 men participated in a 12-wk weight loss intervention. Subjects were matched by age and BMI and randomly assigned to consume 3 g/d of either a soluble fiber supplement (n=14) or placebo (n=15) with a macronutrient energy distribution of approximately 10% carbohydrate, approximately 65% fat, and approximately 25% protein. Because the groups did not differ in any of the variables measured, all da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
2
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 35 publications
9
79
2
6
Order By: Relevance
“…Low-carbohydrate diets have also a great potential in eliminating a larger proportion of abdominal fat (Volek et al, 2004). In addition, carbohydrate restriction can be efficient in significantly lowering both the plasma LDL cholesterol and triglyceride following a twelve-week weight loss intervention (Wood et al, 2006). At the same time, HDL levels can be dramatically increased because of the high-fat consumption included in Atkins diet (Brinkworth, Noakes, Buckley, Keogh, & Clifton, 2009).…”
Section: Benefits Of Fad Dietsmentioning
confidence: 99%
“…Low-carbohydrate diets have also a great potential in eliminating a larger proportion of abdominal fat (Volek et al, 2004). In addition, carbohydrate restriction can be efficient in significantly lowering both the plasma LDL cholesterol and triglyceride following a twelve-week weight loss intervention (Wood et al, 2006). At the same time, HDL levels can be dramatically increased because of the high-fat consumption included in Atkins diet (Brinkworth, Noakes, Buckley, Keogh, & Clifton, 2009).…”
Section: Benefits Of Fad Dietsmentioning
confidence: 99%
“…On the other hand, a low-calorie diet is critical in the treatment of dyslipidemia 34 . Groups CI, D and CD presented reduced TG, LDL and VLDL levels.…”
Section: Discussionmentioning
confidence: 99%
“…Because human studies over the last decade have shown that CR diets improve plasma lipid profiles and reduce atherogenic lipoproteins, we used guinea pigs in the current study to evaluate the effects of CR on the different aspects of the onset and progression of atherosclerosis, such as: lipid accumulation in the aorta, sPLA2 activity, inflammation, and arterial stiffness 18) .…”
Section: Discussionmentioning
confidence: 99%